Practice of Digital Forensic Investigation in the Czech Republic and ISO/IEC 27037:2012 - Jaromír Veber; Zdeněk Smutný; Ladislav Vyskočil (Acta Informatica Pragensia, 2015)
Digital forensics investigation undergone a great transformation in the past two decades. This is due to technological progress and already quite common use of ICT in society. This article deals with the standardization of the procedures for collecting potential digital evidence in connection with the ISO/IEC 27037:2012. This article presents some of the important principles presented in the standard. It also presents the views of two experts from the Czech Republic – criminal police investigator and forensic analyst. They introduce their practical experience regarding the collection and analysis of potential digital evidence and also discuss their views on the content of the standard. This makes it possible to point out the discrepancies between the recommendations laid down in the standard and practice. The general recommendations of the standard are commented in the article with references to some basic procedures used in the Czech Republic for potential digital evidence acquisition and collection.